MORALITY IN LAW: AN ANALYSIS TOWARDS THE LEGAL PHILOSOPHY AND INDONESIA NATIONAL LEGAL SYSTEM - Adhari, Ade; Sitabuana, Tundjung; Aprilia, Indah Siti (Indonesia Law Review, 2023)
The philosophy of law schools, such as positivism and naturalism, always have opposing arguments about moral and law separation. Positivism on one side, believes that morality is a non-law element that has to be strictly separated from the law, while on the other side, naturalism says moral can not be separated from the law and that moral has to become the basis of every law. However, the positivism idea is arduous to be implemented in the current situation as the legal product is constantly managed to conform with the moral values. The objectives of this paper are to study: (1) the moral position according to naturalism, positivism, and interpretivism perspective along with the adjustment of positivism view in morality within the law; and (2) the moral position in Indonesia national legal system as every country has its own legal reasoning pattern about moral in the law. The content of this paper is analyzed using the normative juridical legal research method. The result shows that: (1) Each naturalism, positivism, or interpretivism has its own argument on how morals are found, why morals are important to be incorporated in the law, and what legal goals they most upheld; and (2) Indonesia reasoning pattern exhibits the combination of several philosophy of law schools characteristics. The position of morals in Indonesia alone, has a similarity to naturalism and interpretivism because from the very beginning of law-making process up to the implementation, Indonesia can not separate moral from the law.